Repair of giant omphalocele in a premature neonate with non-cross-linked porcine acellular dermal matrix (Strattice Tissue Matrix) - Helene Engstrand Lilja; Daisy Schulten (Elsevier, 2016)
The management of giant omphalocele (GO) is a major challenge in pediatric surgery and there are many different surgical strategies described. Here we report a complicated case in which the abdominal wall in a premature neonate (gestational age 33 + 2 weeks and 1700 g) with GO was reconstructed with a non-cross-linked acellular porcine dermal matrix (Strattice™) combined with vacuum therapy. This strategy can be an alternative method in the repair of GO in premature neonates with high risk of infection, underdeveloped abdominal cavity and insufficient native tissue.